Gambaran Ketepatan Orotracheal Tube dengan Chula Formula pada Anestesi Umum - Afifah, Ishma Rayhana; Suandika, Made; Susanto, Amin (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
The depth and accuracy of the orotracheal tube are things that must be considered to avoid endotracheal tube malposition. The Chula formula is a method used to predict the accuracy of the orotracheal tube in the right position before intubation. This study aims to determine the accuracy of an orotracheal tube with the Chula formula in general anesthesia. This research method is quantitative with a descriptive observational approach. The sampling technique used total sampling with a total sample of 35 patients undergoing orotracheal tube intubation at Emanuel Hospital. Data was taken by observing the accuracy of the orotracheal tube using the Chula formula during intubation. The results of the study showed that the accuracy of the orotracheal tube with the Chula formula had 100% accuracy. Suggestions for further research are measuring body height directly and applying the chula formula to other tribes.